The Affect of Absence: Rebecca Belmore and the Aesthetico-politics of “Unnameable Affects” - Otto, Elisabeth (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This essay discusses Rebecca Belmore’s work as a form of protest against violence and a memorial for native cultures and compares her performances and their documentation with later installations in galleries. Her work overcomes the dichotomies of presence and absence, of speaking out and silence, and that of image and language with affect that transgresses genres, media, and material.